UPAYA MENINGKATKAN PENGUASAAN KETERAMPILAN BERBAHASA ASING MELALUI METODE MEMORIZE-SPEAK UP-HABITUATION - Sinta Dewi (Educare : Jurnal Ilmu Pendidikan, 2022)
This study aims to analyze and examine the use of the MSH (Memorize-Speak Up-Habituation) method on foreign language mastery skills, especially English. This research uses a descriptive qualitative approach with the type of case study research at the LIPs (Language Intensive Program of SMP Nurul Jadid) Paiton, Probolinggo. The data analysis technique in this study was carried out with the stages of data collection, data reduction, data presentation, and conclusion of research results. From this study, it was found that the MSH method was applied with the stages of Memorize (remembering) new vocabulary and pronunciation; Speak Up (speaking) or integrating the use of new vocabulary in speaking activities (speaking); and Habituation of foreign language activities. This study shows the implication that with the MSH method, LIPs members can master 4 English competencies (listening, writing, reading, speaking) correctly even though it requires high discipline.